An overview of evolution of 3GPP networks - Mohanty, Mihir; Goswami, Laxmi (Materials today : proceedings, 2023)
According to the latest news, the 3rd Generation cooperation Project has been taken the inventiveness of creating aninterworking architecture involving cellular andWLAN as an additional feature to the cellular network requirements of 3GPP. This article provides an overview of an interworking infrastructure that allows mobile operators to provide the public WLAN dependent entrance service to various3GPP network subscribers. The enabling features include 3GPP membership reuse, network availability, authentications relying on 3GPP systems, security keys agreement, USIM /SIM card authorization,user data service access androuting, as well as end-user paying. The function ofinterworkingis accomplished without setting any particular 3GPP specifications for the new WLAN entrance networks, but instead by depend onexisting features available in the traditional WLAN entrance networks centered on the IEEE 802.11 principles. In this paper, authors have focusedon two key aspects of MTC devices,ascurrently discussed in 3GPP-Release 10. These are named as “the control of subscriptions” and the “congestion/overload control of the network”. Anew solution is proposed for the latter onebased on the handling of thebulk signals.